Glycine max as a potential phenol phytoremediator - Zakariya, Syazwani (2015)
There are many reported cases of phenol contamination worldwide. Malaysia itself is also facing the phenol pollution problems. Glycine max from the family Leguminocae and is commonly known as soybean is one of the potential plants that can be used to remediate phenol contaminated areas. The aims of this study were to analyse the potential of G. max in absorbing phenol from phenol- spiked water and to assess the shoots, roots and leaves growth of G. max grown in water spiked with different phenol concentrations. The soybean seeds were germinated and grown in designed system for each respective concentration for six days at room temperature. During the growth period, the elongation of roots, stems and leaves of the soybean plants were measured for every 24 hours by using a standard ruler. The plant morphologies throughout the 6 days were observed. One ml of water sample was collected and subjected to the phenol assay to quantify any remaining phenol in the water. The roots of plants grown in 0.04 g/ L phenol- spiked water were the longest averaging about 17.22 ± 1.23cm. The stem length in 0.04 g/ L phenol was the longest measuring 8.87 ± 0.73 cm. The Control plants exhibited the longest leaves length (1.33 ± 0.60 cm) and the least (0.78± 0.17 cm) was in 0.05 g/ L phenol. No leaves formation could be observed in 0.4 g/ L phenol- spiked water. Phenol at 0.4 g/ L was concluded as high and toxic to the plants since their growths were distorted as early as Day 1. The seeds germinated normally in 0.01, 0.04 and 0.05 g/ L phenol water. Abnormal growth of the plants could be noted at three respective phenol water concentrations which were 0.1, 0.2 and 0.4 g/ L. Plants absorbed 100% phenol at different rates except for 0.04 g/ L, only half (0.20 g/ L) of the phenol was successfully absorbed by the plants on Day 3. The fastest absorption was detected at 0.2 g/ L whereby the plants absorbed all the phenols within 5 days at a rate of 0.00170 g/ L/ hour meanwhile, the slowest rate was at 0.01 g/ L. G. max was classified as a phytodegrader in group of phytoremediator since the phenol content in plant tissues after being treated with phenols showed reduction in amount.